High seroprotection rates and geometric mean titre increases after repeated annual influenza vaccinations in a cohort of HIV-infected adults in Austria. Issue 29 (23rd June 2022) - Kitchen, Maria; Leierer, Gisela; Kistner, Otfried; Wodal, Walter; Gisinger, Martin; Zangerle, Robert; Sarcletti, Mario
Abstract: Introduction: Vaccination against seasonal influenza is recommended for all HIV-infected persons. Few data have been reported on the effect of repeated annual vaccination in this population. Methods: We measured haemagglutination inhibition antibody responses and investigated seroprotection rates in 344 HIV-infected adults before and 12 weeks after influenza vaccination with a trivalent subunit vaccine. Results: 68.3% of patients were male, the median age was 45 years. 83.7% had a viral load < 50 copies/mL. The median CD4 count was 604/µL. 304 patients (88.4%) had received influenza vaccinations in previous years. Seroprotection rates for A/H1N1 and B were over 90% in all age groups before vaccination and close to 100% after vaccination. For A/H3N2, seroprotection rates were lowest in individuals below 30 years both before and after vaccination (22.2% and 50.0%) and higher in older age groups (48.4% and 83.9% in people over 60 years). GMT fold increases were not significantly different across the age groups (3.0 to 4.2, p = 0.425). Previous influenza vaccinations were associated with higher seroprotection rates before and after vaccination (62.2% and 84.2% in patients with 8 or more previous vaccinations vs. 15.0% and 57.5% without previous vaccinations, respectively). Individuals with detectable viral load, elevated immune activation (urine neopterin ≥ 250 µmol/mol creatinine), and higher CD4 nadir (≥200 cells/µL) showed a trend towards inferior immune responses to vaccination, whereas gender and CD4 count did not have an effect. Conclusion: The lower seroprotection rates observed in younger individuals may be explained by the higher proportion of patients without HIV treatment and with fewer previous encounters with influenza strains. Good seroprotection rates can be achieved in elderly HIV-infected patients and after repeated annual vaccinations.